Optimizing Strategies for Family Pastoral Counseling in Local Church Contexts - Kaensige, Mariska Theodora; Brek, Yohan; Raintung, Agnes B.J. (Peneliti.net, 2025)
This study explores the strategic optimization of family pastoral counseling within the context of KGPM Bukit Sion Tumumpa, a local church facing increasing pastoral challenges. Using a qualitative descriptive approach, the research employed field observations, interviews, and documentation to uncover the current state of counseling practices. Findings revealed three core issues: the absence of a structured system for counseling delivery, insufficient counseling competence among church leaders, and a lack of emotional safety for congregants seeking help. Counseling was often reactive, undocumented, and reliant solely on pastoral availability, without support from elders or deacons as mandated by church governance. Moreover, counseling literacy was minimal, and trust barriers due to gossip or judgment further discouraged congregants—particularly women and youth—from seeking support. These findings underscore the need for systemic reform, including scheduled pastoral visits, competency-based training, and the cultivation of safe, confidential spaces within the church. By addressing these gaps, local churches can transform pastoral counseling into a redemptive ministry that strengthens family units and enhances spiritual growth.